CORRELATION BETWEEN LIVER SEGMENTAL ANATOMY AND THE PATTERN OF HEPATIC INVOLVEMENT IN CHRONIC HEPATITIS B PATIENTS - Dr Qurat ul Ain Khan; Dr Talat Yasmeen; Dr Samar Ekram; Gulraiz Karim Rind Baloch; Dr Madiha Imtiaz; Dr Farah Malik; Emaan Mansoor; Ezza Mansoor; Efrah Mansoor; Dr Afsheen Mansoor (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Chronic hepatitis B virus (HBV) infection can lead to progressive liver damage and complications, but the distribution of hepatic involvement across different liver segments remains understudied.Objective: To evaluate the correlation between liver segmental anatomy and the pattern of hepatic involvement in patients with chronic hepatitis B using radiological imaging. Methods: This descriptive cross-sectional study was conducted at private hospitals of Karachi from October 2024 to March 2025. A total of 198 patients diagnosed with chronic hepatitis B were included in the study through non-probability consecutive sampling. After obtaining informed consent, demographic and clinical data including age, sex, duration of HBV infection, liver function test results, and antiviral treatment history were recorded using a structured proforma.Results: The mean age was 44.6 ± 11.2 years; 62.6% were male. Segment VI was the most commonly involved (71.7%), followed by segments VII (65.2%) and V (63.1%), whereas segment I was least involved (14.1%). Patients with moderate-to-severe disease showed significantly higher involvement of posterior segments (p < 0.001). Fibrosis was most prevalent in segments VI (76.5%) and VII (67.6%). Regenerative nodules were predominantly found in segment VIII (57.1%). Inter-observer agreement for segmental analysis was substantial (Cohen’s Kappa = 0.81).Conclusion: It is concluded that chronic HBV infection exhibits a preferential pattern of hepatic involvement, predominantly affecting posterior liver segments. Segmental imaging evaluation can aid in early recognition of disease progression and may enhance personalized management strategies for HBV patients.